Hydrological regime index for non-perennial rivers - P. F. Dornes; R. N. Comas (Hydrology and Earth System Sciences)
The hydrological regime is an integrated basin response that constitutes an established paradigm for environmental flows (e-flows) to mimic as all its components influence aquatic life and consequently fluvial ecosystems. It has been widely described that human activities and climate change modify the natural hydrological regime. These changes in non-permanent rivers generally tend towards greater intermittency, a condition that limits the applicability of hydrological alteration indices. The general aim of the paper is to develop an aggregated impact index, the hydrological regime index (HRI), suitable for flow alteration assessment in non-permanent rivers. The HRI is composed of the flow magnitude attenuation, timing of maximum flow, and interannual flow variation impact factors. The HRI is based on simple conceptualizations and uses monthly flow data, allowing for its applicability in basins with limited information. The HRI was suitable to evaluate the impacts on the river regime of both the Desaguadero–Salado–Chadileuvú–Curacó River, which is severely dammed with intermittent runoff, and the Colorado River, with permanent runoff. In all the cases, the HRI successfully distinguished different impacts on the hydrological regime under natural and low- and high-impoundment conditions. Thus, the HRI constitutes a very useful tool for determining e-flows and quantifying impacts due to water or land use changes.